PEMANFAATAN LIMBAH DALAM MENDUKUNG PROGRAM KAMPUNG IKLIM (PROKLIM) - Aziz, Ervan; Prihatini, Lishapsari; Nurwahyuliningsih, Eka (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STISIPOL Candradimuka, 2022)
Adaptation and mitigation are one of the efforts that can be carried out by various parties in dealing with climate change, one of which is that the community as the affected population must be actively involved in these efforts. The government has committed to addressing this problem by presenting a climate village program (ProKlim) with the aim of encouraging community participation as a whole in increasing their ability to adapt to the impacts of climate change and reducing greenhouse gas emissions. One of the ProKlim programs to prevent climate change is by utilizing waste from used goods. This activity uses a community-based approach, meaning that it actively involves the community to participate in the activity. The implementation method consists of location surveys, observations, transects (tracing), FGDs, seminars and training. The results of community service activities have a positive impact on the community, because they gain new knowledge and skills regarding the use of used tire waste which can reduce negative impacts on the environment and can be used sustainably by turning the waste into recycled materials such as flower pots. This activity not only reduces environmental pollution but can also help economic circulation and create new business opportunities.